Molecular systematics and antifreeze biology of sub-Antarctic notothenioid fishes - Miya, Tshoanelo Portia (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2014)
Fishes of the perciform suborder Notothenioidei are found in Antarctic and sub-Antarctic waters that are separated by the Antarctic Polar Front (APF), with some species being distributed on both sides of this front. In this wide latitudinal range, these fishes are exposed to different temperatures ranging from -2 Â°C in the High Antarctic regions to 12 Â°C in the sub-Antarctic regions. To survive in icy Antarctic waters, the Antarctic notothenioid species have evolved antifreeze glycoproteins (AFGPs) that prevent their body fluids from freezing. The findings of past research on the AFGP attributes of several notothenioid species inhabiting ice-free sub-Antarctic environments have presented a complex picture. Furthermore, previous taxonomic studies split widely distributed notothenioids into different species and/or subspecies, with other studies disagreeing with these splits. To understand the response of the sub-Antarctic notothenioids to warmer, ice-free environments, it is necessary to have a good understanding of their antifreeze biology and systematics. Therefore, this study aimed to determine the association, if any, between the antifreeze attributes of sub-Antarctic notothenioid fishes and their taxonomic status. And more...
Keywords: Nototheniidae; Antifreeze proteins; Nototheniidae -- Classification -- Molecular aspects; Polyacrylamide gel electrophoresis